INTEGRATION OF THE "JAK BEUT" PROGRAM IN CHARACTER DEVELOPMENT OF ELEMENTARY SCHOOL STUDENTS: A CONTEXTUAL STUDY IN WEST ACEH - Hendra SH; Nur Rohman; Uswatun Hasanah (NIZHAMIYAH, 2025)
This study examines the role and integration strategy of Jak Beut activities in fostering the character of Elementary school students in West Aceh. Jak Beut is a non-formal education tradition of the Acehnese people that focuses on the teaching of the Qur'an, moral values, and morals. Although not tied to the formal curriculum system, this activity still exists and significantly contributes to developing students' character. The research uses a qualitative approach of case studies with data collection techniques through in-depth interviews, participatory observation, and documentation. The informants included madrasah teachers, Jak Beut, students, parents, and local Ministry of Religion officials. The study results show that Jak Beut plays an active role in shaping the values of discipline, responsibility, good manners, social care, and teacher respect. This activity strengthens character learning that has been taught in madrasas. However, integration challenges arise due to the lack of formal regulations that accommodate the existence of Jak Beut in the national education system and the lack of collaboration between madrasah and madrasah institutions. Therefore, policymakers must strategically bridge the locality-based formal and traditional education. This study concludes that Jak Beut is a source of contextual character education that is relevant and worthy of being used as a strategic partner of madrasas in forming a generation with Islamic character and culture.